Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1478-3231.2011.02722.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient time costs and out‐of‐pocket costs in hepatitis C

Abstract: Background Hepatitis C virus (HCV) infection is associated with substantial costs to patients, their caregivers and society. Aims We evaluated time costs (time spent seeking healthcare) and out‐of‐pocket (OOP) costs for patients with HCV and their caregivers. Methods We measured costs for 738 HCV outpatients in a tertiary‐care clinic using a patient‐completed questionnaire. Time and OOP costs were compared across disease stages and sociodemographic categories. We examined the association between cost and disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Additionally, data on time and productivity costs for HCV patients were sparse compared to the data available for direct health costs that are frequently used in CEAs for these drugs. We used published estimates for time and productivity (absenteeism and presenteeism) costs from a study of 306 HCV patients compared with propensity matched controls using the Work Productivity and Activity Impairment questionnaire [36,37]. This self-reported time and productivity loss may overestimate actual productivity losses [58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, data on time and productivity costs for HCV patients were sparse compared to the data available for direct health costs that are frequently used in CEAs for these drugs. We used published estimates for time and productivity (absenteeism and presenteeism) costs from a study of 306 HCV patients compared with propensity matched controls using the Work Productivity and Activity Impairment questionnaire [36,37]. This self-reported time and productivity loss may overestimate actual productivity losses [58].…”
Section: Discussionmentioning
confidence: 99%
“…This self-reported time and productivity loss may overestimate actual productivity losses [58]. The patient and caregiver time costs were combined to be consistent with the way in which the original study collected this information and the way results were reported in their final regression model [36]. The time costs estimates used in our analysis were from a study of 738 HCV outpatients in Canada, potentially limiting the generalizability to time costs in the US despite our conversion and inflation adjustments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important knowledge has been obtained in other medically ill populations by eliciting patient perspectives on their access to medical care and treatment experi-ences. In contrast, research to date on barriers to treatment for HCV has been conducted largely from the perspective of the physician or healthcare delivery system [20]. In contrast, research to date on barriers to treatment for HCV has been conducted largely from the perspective of the physician or healthcare delivery system [20].…”
Section: Introductionmentioning
confidence: 99%
“…The OOP cost for patients who undergo DAA treatment is currently unknown, may vary considerably by insurance status, and is an important informational need for patients' contemplating HCV treatment 49 . The medical cost literature describes the importance of measuring both direct and indirect costs related to treatment 50 .…”
Section: 0 Methodsmentioning
confidence: 99%